2016
DOI: 10.1039/c6ew00179c
|View full text |Cite
|
Sign up to set email alerts
|

A consilience model to describe N2O production during biological N removal

Abstract: A mathematical model congruent with the current understanding of the biological processes occurring during wastewater treatment operations is proposed.Please check this proof carefully. Our staff will not read it in detail after you have returned it.Translation errors between word-processor files and typesetting systems can occur so the whole proof needs to be read. Please pay particular attention to: tabulated material; equations; numerical data; figures and graphics; and references. If you have not already i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…To date, most genome-scale and metabolic models of nitrification have focused on biotic reactions (17, 22, 23, 36). While this approach simplifies the construction of models, it neglects the importance of abiotic chemistry in the N cycle (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, most genome-scale and metabolic models of nitrification have focused on biotic reactions (17, 22, 23, 36). While this approach simplifies the construction of models, it neglects the importance of abiotic chemistry in the N cycle (13).…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of nitrifier-derived emissions of N oxides generated by nitrification from soils and engineered environments are extremely variable and depend on a variety of environmental conditions such as the rate of nitrification, pH, temperature, and oxygen (O 2 ), among other factors (4, 13, 1821). Recent modeling efforts by Perez-Garcia et al and others have sought to understand conditions that generate N oxides through single and multispecies metabolic network models of wastewater treatment systems (17, 2224). Modeling N oxide production by simplified communities of model nitrifiers in both single culture and coculture, including abiotic reactions, can expand on previous work to better explain the mechanisms and conditions that affect N oxide gas emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the AD is framed using the widely used anaerobic digestion model no 1 (ADM1) [25]. Further to extend the study of carbon recovery impact on N 2 O emission, two different models (as shown in Figure 8 ) are considered which are extension of Hiatt and Grady [26], Guo and Vanrolleghem [27] and Domingo-Félez and Smets [28]. For additional details on design and operating conditions, the reader is referred to the papers by Gernaey et al [18] and Jeppsson et al [19].…”
Section: Modified Bsm2 Plant Layout and Simulation Strategymentioning
confidence: 99%
“…In oder to understand the impact of carbon recovery (by RBF and PC) on N 2 O gas emission, the ASM1 model is extended (to incorporate the one pathway and two pathway model separately) based on the understanding from Hiatt and Grady [26], Guo and Vanrolleghem [27] and Domingo-Félez and Smets [28]. In this section, it is important to note that these N 2 O models are only used to generate N 2 O emission data for the discussion section in the results (see the Table 7).…”
Section: The N 2 O Model -Using One Pathway and Two Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation